Impact of Body Weight on Self-Esteem among Undergraduate Young Adult Students of Doctor of Physiotherapy, Karachi - Anum Naz, Farhan Ishaque, Samreen Yasmeen, Erum Naz, Rida Afzal, Fazila Khan, Anum Naz, Farhan Ishaque, Samreen Yasmeen, Erum Naz, Rida Afzal, Fazila Khan (Journal of Rawalpindi Medical College, 2022)
Objectives: To determine the recurrence of body disappointment, loss of control and self- related wellbeing in interpose the relationship among body weight and impairments in self-esteem among students of Doctor of Physiotherapy (DPT) Material and Methods: The research was among youthful understudies of the two sexes (boys and girls) of Doctor of Physiotherapy in both campuses—removed for blind review—. Concluded an overview through the questionnaire (Rosenberg Self-Esteem Scale according to the sample size of 298 computed through online programming Open Epi. The survey was acknowledged globally and it was standardized questionnaire. The data was assembled by figuring the BMI among body weight understudies of (DPT) and to check the level of self-esteem by Rosenberg Self-Esteem Scale. The survey conducted from January 2019 to February 2019. Results: Normal weight was adjusted to 18.50 till 24.90 – a total of 81 respondents, Overweight was adjusted to 25.00 till 29.90 of 35 respondents, obese category was adjusted to 30.00 or more a total of 17 respondents were adjudged to be in this category as per weigh ranges BMI. After analyzing the Chi-Square tabulation, it was found that the highest self-esteem was found in the normal weight BMI category respondents followed by the overweight category and the lowest self-esteem was found in obese category. As the table shows that girls have more self-esteem as compared to the boys, although the girl’s respondents are more so than boys are. Conclusion: It has been conclude that the proportion of the highest self-esteem were found in the normal weight BMI category respondents followed by the overweight category and the lowest self-esteem was found in obese category. Keywords: Body Mass Index, Stress, Obesity, Body image, Depression and Self-esteem.